Lesiones con arma corto-punzante desde la perspectiva de la dactiloscopia (2016)
The historical evolution of fingerprinting has always been focused as the ID in humans, currently the fingerprint displayed in one of the biometric technologies most commonly used to be considered a safe and effective method to control access in and out authorize sensitive operations, this thanks to that is unique in every human being and with the elapse of time, technological advances will be our digital signature.The role of the investigator of the crime on several occasions culminates in the judicial bench, where considerations that allow criminalistics be considered a science, in the development of the case investigation dactyloscopy as one of the disciplines were applied addresses criminalistics, carrying out the respective procedure for the investigated fact and evidence may clarify the crime